The Effect of Self-Regulated Learning Psychoeducation on Improving Self-Regulated Learning and Academic Achievement among Students at SMP Negeri 4 Sumbawa - Rahmad Akbarsyah; Djudiyah (Kirana Publisher (KNPub), 2026)
Academic achievement is one of the important indicators of students' success in the educational process.Students' academic achievement is not only influenced by external factors, such as learning environmentsand teaching methods, but also by internal factors related to students' ability to manage their own learningprocesses. One of the psychological factors that plays an important role in learning activities is selfregulated learning (SRL), which refers to an individual's ability to plan, monitor, control, and evaluate theirlearning activities independently. Low levels of self-regulated learningmay cause students to experiencedifficulties in managing study time, maintaining academic motivation, and achieving optimal learningoutcomes. Therefore, an intervention through self-regulated learning psychoeducation is needed to helpstudents improve their ability to regulate their learning processes.This study aims to determine the effectof self-regulated learning psychoeducation on improving students' academic achievement at SMP Negeri 4Sumbawa. This study employs a quantitative approach using an experimental method with a one-grouppretest-posttest design. The participants of this study are planned to consist of approximately 30–50students from SMP Negeri 4 Sumbawa who meet the research criteria. Data collection will be conductedusing a self-regulated learning scale, documentation of students' academic scores, and measurementsconducted before and after the psychoeducational intervention. Data analysis will be performed usinginferential statistical analysis with a paired sample t-test to examine differences in students' learningabilities before and after the intervention. The expected results of this study indicate that self-regulatedlearning psychoeducation can improve students' ability to manage their learning processes, increaseacademic motivation, and positively influence academic achievement. This research is expected tocontribute to the field of educational psychology, particularly regarding the implementation ofpsychological interventions to develop students' independent learning abilities and improve their academicperformance.